Electro-Fenton cathode based on MOF (Metal Organic Framework) derived carbon as well as preparation method and application of electro-Fenton cathode

By using the Fe3O4/Fe0/Fe3C composite components of MOF-derived carbon in the electrofenton cathode, the problems of low efficiency and poor stability of traditional iron-based catalysts are solved, and efficient antibiotic degradation and electrode stability are achieved.

CN119263413AActive Publication Date: 2025-01-07BEIJING UNIV OF CHEM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411767370.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Traditional iron-based catalysts have problems such as high leaching concentration, low catalytic efficiency and difficulty in recycling in the electrofenton method, which makes it difficult to practically apply the electrofenton method, and the preparation of highly active iron-based MOF-derived carbon is challenging.

Method used

Using Fe3O4/Fe0/Fe3C electrofenton cathode based on MOF-derived carbon, the Fe3O4, Fe0 and Fe3C composite components are formed on the penetrating electrode matrix to promote H2O2 activation and OH generation, and form a protective shell through calcination to increase catalyst stability. sex.

Benefits of technology

The degradation rate and removal efficiency of tetracycline are improved, and the electrode can be recycled, and the removal rate is maintained above 80%, extending the service life of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263413A_ABST
    Figure CN119263413A_ABST
Patent Text Reader

Abstract

The invention discloses an electro-Fenton cathode based on MOF derived carbon and a preparation method and application thereof.The electro-Fenton cathode comprises a transmission type electrode base body and an MOF derived carbon material located on the surface of the transmission type electrode base body, the MOF derived carbon material comprises a carbon shell and a composite component in the carbon shell, and the electro-Fenton cathode is characterized in that the composite component comprises Fe3O4, Fe0 and Fe3C. The electro-Fenton cathode contains Fe < 3 > O < 4 > and also contains high-activity components of Fe < 3 > C and Fe < 0 >, so that H2O2 is promoted to be activated to generate. OH, a protective shell can be formed, iron ions in the electrode are prevented from being leached, and the stability of the whole catalyst is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of advanced oxidation technology, and in particular to a Fe3O4 / Fe 0 / Fe3C electro-Fenton cathode and its preparation method and application. Background Art

[0002] Since the discovery of antibiotics, they have been widely used in the treatment of human and animal diseases. The use of antibiotics has increased year by year, and they inevitably enter the environment, causing water pollution. Since antibiotic molecules are relatively stable, it is difficult to completely degrade them by traditional processes. Therefore, the degradation of antibiotics in water has attracted widespread attention.

[0003] The electro-Fenton process is a type of advanced oxidation process with the characteristics of strong controllability, fast reaction rate and high degradation efficiency. The electro-Fenton process mainly generates H2O2 in situ through a two-electron reduction reaction of O2 at the cathode, and then H2O2 is further decomposed into ·OH by the catalyst to oxidize and degrade pollutants in water. In the electro-Fenton system, the properties of the electrode material are the main factor affecting the degradation efficiency of the electro-Fenton process. In recent years, various electrode materials have been widely studied, among which iron-based catalysts have been widely studied due to their low cost and good environmental compatibility. However, traditional iron-based catalysts have problems such as high leaching concentration, low catalytic efficiency and difficulty in recovery, which makes the electro-Fenton process difficult to apply in practice. Metal-organic framework (MOF) consists of metal centers and organic ligands, has excellent catalytic activity, tunable crystals and high porosity, and has great application prospects in the field of catalysis. After further calcination, it is converted into a MOF-derived carbon structure, which consists of porous carbon embedded with metals, metal oxides or metal carbides, enhances conductivity, accelerates electron transfer and improves stability. Iron-based MOFs have abundant unsaturated sites, which can be used as active sites for catalyzing the conversion of H2O2 to ·OH in the Fenton system. After further carbonization, the resulting iron-based MOF has better electron transfer ability and higher stability, so it is widely used in the Fenton system. However, in the traditional preparation process of iron-based MOF-derived carbon, only less active iron oxide can be generated. Therefore, the preparation of highly active iron-based MOF-derived carbon is still challenging. Summary of the invention

[0004] 1. Purpose of the invention The purpose of the present invention is to provide an electro-Fenton cathode based on MOF-derived carbon and a preparation method and application thereof, wherein the electro-Fenton cathode contains Fe3C and Fe in addition to Fe3O4. 0 Highly active ingredients not only promote the activation of H2O2 to generate OH, but also form a protective shell to prevent the leaching of iron ions inside the electrode, thereby increasing the stability of the entire catalyst.

[0005] (II) Technical solution In order to solve the above problems, the first aspect of the present invention provides an electro-Fenton cathode based on MOF-derived carbon, comprising a penetrating electrode substrate and a MOF-derived carbon material located on the surface of the penetrating electrode substrate, wherein the MOF-derived carbon material comprises a carbon shell and a composite component in the carbon shell, wherein the composite component comprises Fe3O4, Fe 0 and Fe3C.

[0006] The penetrating electrode matrix refers to an electrode matrix through which liquid can pass while flowing during the reaction process.

[0007] The electro-Fenton cathode provided in the embodiment of the present invention contains not only Fe3O4 but also Fe3C and Fe 0 Highly active ingredients not only promote the activation of H2O2 to generate OH, but also form a protective shell to prevent the leaching of iron ions inside the electrode, thereby increasing the stability of the entire catalyst.

[0008] In a second aspect, the present invention provides a method for preparing an electro-Fenton cathode based on MOF-derived carbon, comprising: Step 1: reacting a mixed reaction system containing a penetrating electrode substrate, an iron source, an organic ligand, sodium hydroxide, a regulator, and a solvent to form an iron-based MOF material on the surface of the penetrating electrode substrate, wherein the regulator is used to regulate the morphology and defects of the surface of the iron-based MOF material; Step 2: calcining the penetrating electrode substrate with iron-based MOFs material formed on the surface obtained in step 1 to obtain an electric Fenton cathode based on MOF-derived carbon, wherein the specific conditions of the calcination include a calcination temperature of not less than 600°C.

[0009] In the embodiments of the present invention, the formation method of the iron-based MOFs material includes but is not limited to in-situ growth.

[0010] Specifically, the regulator is selected from at least one of formic acid, acetic acid, and hydrofluoric acid; Based on the volume of the solvent being 100%, the amount of the regulator added is 0.1-30%.

[0011] In a preferred embodiment, the regulator is acetic acid; Preferably, the amount of the regulator added is 2-6%, which can ensure that the degradation rate of tetracycline in the prepared electro-Fenton cathode can reach more than 80%, can be recycled 3 times, and the removal rate is maintained at more than 60%; More preferably, the amount of the regulator added is 4-6%, which can ensure that the degradation rate of tetracycline in the prepared electro-Fenton cathode can reach more than 97%, and can be recycled 6 times with the removal rate still maintained at more than 80%.

[0012] Specifically: the penetrating electrode substrate is selected from at least one of a stainless steel mesh, a copper mesh, a nickel mesh, a cobalt mesh, and a titanium mesh; The iron source is selected from at least one of ferric nitrate, ferric chloride and ferrous chloride; The organic ligand is selected from at least one of terephthalic acid, fumaric acid and trimesic acid; The solvent is selected from at least one of methanol, N,N-dimethylformamide, and deionized water; The mass ratio of the iron source to the organic ligand is 0.5-5:1, the mass of the sodium hydroxide is 0.1-5 times that of the iron source, and the mass of the solvent is 10-120 times that of the iron source.

[0013] Preferably, the mass ratio of the iron source to the organic ligand is 0.8-2:1, the mass of sodium hydroxide is 0.2-1 times that of the iron source, and the mass of the solvent is 50-100 times that of the iron source.

[0014] Specifically, the specific conditions of the reaction in step 1 include: The reaction temperature is 20~200℃; The reaction time is 2~200 h.

[0015] Specifically, the specific conditions for calcining in step 2 include: The method is carried out under an inert atmosphere; the inert atmosphere is selected from at least one of carbon dioxide, nitrogen and an inert gas; Calcination temperature is 600~1000℃; The calcination time is 0.5~10 h.

[0016] Calcination under this condition can ensure that the obtained electrode can achieve a degradation rate of tetracycline of more than 80% when used as an electro-Fenton cathode, and can be recycled three times with the removal rate still maintained at more than 60%.

[0017] Preferably, the calcination temperature of step 2 is 600-700°C, and the calcination time is 3-4 h. Calcination under such conditions can ensure that the degradation rate of tetracycline by the obtained electro-Fenton cathode can reach more than 97%, and it can be recycled 6 times, and the removal rate remains above 80%.

[0018] In one embodiment, a method for preparing an electro-Fenton cathode based on MOF-derived carbon is provided, which specifically comprises: Step 1: Dissolve the iron source and the organic ligand in a solvent to form a suspension.

[0019] Step 2: Add a certain amount of regulator and sodium hydroxide solution to the suspension obtained in step 1.

[0020] Step 3: Place the pretreated stainless steel mesh into the suspension obtained in step 2 and transfer it to the reactor.

[0021] Step 4: Place the reactor in step 3 in an oven and heat it.

[0022] Step 5: After cooling, open the reactor in step 4, take out the obtained stainless steel mesh electrode grown with iron-based MOF, rinse it with a solvent, and put it in an oven to dry.

[0023] Step 6: Place the stainless steel mesh electrode dried in step 5 into a tubular furnace and calcine it. After cooling, the target electrode is obtained.

[0024] In this embodiment, sodium hydroxide is added in the form of a solution, and the concentration of the sodium hydroxide solution is preferably 0.1-10 M; Based on the volume of the solvent used in step 1 being 100%, the amount of the hydroxide solution added is 0.1% to 30%.

[0025] The third aspect of the present invention provides the use of the above electrode and the electrode prepared by the above preparation method in catalytic degradation of antibiotics.

[0026] Specifically, the antibiotic is preferably tetracycline.

[0027] In one embodiment, the antibiotics are dissolved in water to prepare sewage with a concentration of 0.01-15 mg / L, and then the sewage is poured into the reactor, the DC power supply is turned on, and the current density of the gas diffusion electrode and the composite electrode cathode is controlled. The current density of the gas diffusion electrode ranges from 0.1 to 100 mA / cm 2 The current density of the catalytic cathode ranges from 0.1 to 20 mA / cm 2 , and finally the degradation time is controlled to be 10~180 min to achieve the degradation of pollutants.

[0028] (III) Beneficial effects The above technical solution of the present invention has the following beneficial technical effects: The preparation method provided by the present invention uses a regulator to induce defects in the in-situ grown MOF, and then further calcines the MOF precursor at a temperature not less than 600°C to obtain a composite structure electric Fenton cathode, wherein the electric Fenton cathode contains Fe3C and Fe in addition to Fe3O4. 0 , where Fe3O4 / Fe 0 It can effectively provide catalytic active sites for H2O2 and promote the activation of H2O2 to generate ·OH. When the electro-Fenton cathode removes tetracycline, the removal efficiency is greatly improved. At the same time, the Fe3C in the electrode can form a protective shell to prevent the leaching of internal iron ions and increase the stability of the entire catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The Fe3O4 / Fe 0 / Fe3C electro-Fenton cathode. a and b are scanning electron microscope images at different magnifications.

[0030] Figure 2 X-ray diffraction patterns of the electric Fenton cathodes provided in Example 1 and Comparative Example 1 of the present invention; Figure 3 X-ray diffraction patterns of the electric Fenton cathodes provided for Examples 1-3 of the present invention and Comparative Example 2; Figure 4 X-ray diffraction patterns of the electric Fenton cathodes provided in Examples 1 and 4 of the present invention and Comparative Example 3; Figure 5 The Fe3O4 / Fe 0 / High-resolution transmission electron microscopy image of the Fe3C electro-Fenton cathode; Figure 6 It is a schematic diagram of the device used in the application of the present invention; Figure 7 The degradation effect diagram of tetracycline by the electro-Fenton cathode provided in Examples 1-3 and Comparative Example 2 of the present invention, wherein a is a tetracycline removal efficiency diagram, and b is a kinetic fitting curve diagram of the degradation process; Figure 8 The degradation effect diagram of tetracycline by the electro-Fenton cathode provided in Examples 1 and 4 of the present invention and Comparative Example 3, wherein a is a tetracycline removal efficiency diagram, and b is a kinetic fitting curve diagram of the degradation process; Fig. 9 The Fe3O4 / Fe 0 / Fe3C electro-Fenton cathode recycling test results. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0032] The raw materials and reagents used in the embodiments of the present invention are all conventional commercially available products.

[0033] Among them, the aperture of the stainless steel mesh is 100 mesh.

[0034] Example 1 Fe3O4 / Fe 0 Preparation of Fe3C electro-Fenton cathode: Step a: Pretreat the stainless steel mesh by cutting the mesh into 3×3 cm pieces and placing it in 10% diluted hydrochloric acid, ultrasonically treating it for 2 min, rinsing it three times with ultrapure water, and then placing it in 10% sodium hydroxide solution, ultrasonically treating it for 2 min, rinsing it three times with ultrapure water, and finally drying it in a 60°C oven.

[0035] Step b: dissolving 0.56 g of FeCl3·6H2O and 0.33 g of terephthalic acid in 50 mL of N,N-dimethylformamide to obtain a mixed solution; Step c: Place the stainless steel mesh pretreated in step a into the mixed solution obtained in step b, and add 4 mL of sodium hydroxide solution (2 M) and 2 mL of acetic acid to obtain a reaction system, and place the obtained reaction system into a reactor and heat it to 110° C. and maintain it for 24 h to obtain a Fe-MOF stainless steel mesh.

[0036] Step d: The Fe-MOF stainless steel mesh obtained in step c was dried in an oven at 60°C, and then placed in a tubular furnace filled with argon gas, and calcined at 600°C at a rate of 5°C / min for 3 h. After the tubular furnace was cooled naturally, Fe3O4 / Fe 0 / Fe3C electro-Fenton cathode.

[0037] Embodiment 2~4 Examples 2 to 4 respectively provide an electro-Fenton cathode, and the preparation method thereof is basically the same as that of Example 1, and the differences are shown in Table 1.

[0038] Table 1 Experimental conditions of Examples 1 to 4 Example Example 1 Example 2 Example 3 Example 4 Amount of acetic acid added (v / v) 4% 2% 6% 4% Calcination temperature (℃) 600 600 600 700 Degradation rate of tetracycline 97.7% 84.7% 97.2% 97.0% Comparative Example 1 The process is basically the same as Example 1, except that step d is not performed and only the Fe-MOF stainless steel mesh is obtained.

[0039] Comparative Example 2 The process is basically the same as Example 1, except that acetic acid as a regulator is not added in step c.

[0040] Comparative Example 3 The process is basically the same as Example 1, except that the calcination temperature in step d is 400°C.

[0041] Characterization of the electrodes provided in each embodiment and comparative example The scanning electron microscope image of the electric Fenton cathode provided in Example 1 is as follows Figure 1 As shown. Figure 1 a It can be seen that Fe3O4 / Fe 0 / Fe3C is grown in situ on a stainless steel mesh by Figure 1b It can be seen that after calcination at 600℃, Fe3O4 / Fe 0 / Fe3C has a uniform crystal structure and retains the original crystal form of Fe-MOF, indicating that the pore structure of the material is still retained during the calcination process.

[0042] Figure 2 The Fe3O4 / Fe 0 The X-ray diffraction patterns of the Fe-MOF cathode provided in the comparative example 1 and the Fe3O4 / Fe3C electro-Fenton cathode show that the derivative peaks of Fe-MOF at 2θ=9.12, 10.72, 20.02, and 21.56° correspond to the (002), (101), (202), and (211) crystal planes, indicating that the prepared Fe-MOF is MIL-88B (Fe). 0 The X-ray diffraction pattern of the / Fe3C electrode has diffraction peaks at 2θ=18.3, 30.2, 35.5, 57.1 and 62.7°, which correspond to the (111), (220), (311), (511) and (440) planes of Fe3O4 crystals, indicating that after calcination, part of MIL-88B (Fe) is converted into Fe3O4, and the diffraction peaks at 2θ=44.6 and 65.0° correspond to the (111), (220), (311), (511) and (440) planes of Fe3O4 crystals. 0 The (110) and (200) crystal faces of the crystals correspond to each other, indicating that after the regulation of acetic acid, the Fe in the MOF precursor has a higher activity and can react with carbon under calcination conditions. Therefore, part of the Fe is reduced to zero-valent iron, and Fe 0 The generation of Fe 3+ Fe 2+ The conversion of H2O2 to ·OH can be further promoted. The diffraction peaks at 2θ = 26.4°, 42.9°, 43.7°, 59.7° and 69.5° correspond to the (020) (211) (102) (311) and (042) crystal planes of Fe3C, which proves that the organic ligands are carbonized during the calcination process and react with part of the highly active Fe to form Fe3C crystals. The appearance of Fe3C crystals can prevent the active sites inside the catalyst from directly contacting the reaction solution, thereby enhancing the stability of the catalyst.

[0043] Figure 3 The X-ray diffraction patterns provided for the electric Fenton cathodes provided in Examples 1-3 and the electric Fenton cathodes provided in Comparative Example 2 show that at the same calcination temperature, when the addition amount of acetic acid is 0%, the main crystal form of the material is Fe3O4, and there is a small amount of Fe3C crystal form. When the addition amount of acetic acid is 2%, the diffraction peak of Fe3C gradually increases, and Fe3C appears at 2θ=44.6°. 0The diffraction peaks of the catalyst indicate that after the regulation of the crystal form, the Fe in the catalyst is more likely to combine with carbon at high temperature to form a stable Fe3C structure, and in the presence of high-temperature carbon, the Fe in the material is more likely to be reduced to Fe 0 As the addition amount of acetic acid increases to 4% and 6%, Fe3C and Fe 0 The diffraction intensity of the ions was significantly enhanced, indicating that after being regulated by the regulator, Fe was more likely to react with carbon to generate low-valent iron or iron carbide. Therefore, the results of X-ray diffraction proved that by adding acetic acid as a regulator, Fe that promotes the generation of ·OH can be generated under calcination conditions. 0 and Fe3C which increases the catalyst stability.

[0044] Figure 4 The X-ray diffraction diagrams provided for the electric Fenton cathodes provided in Examples 1 and 4 and the electric Fenton cathodes provided in Comparative Example 3 show that when the calcination temperature is 600-700°C, the crystal form of the electrode contains Fe3O4, Fe 0 , Fe3C three components.

[0045] Figure 5 The Fe3O4 / Fe 0 / Fe3C electro-Fenton cathode high-resolution transmission electron microscope image, as shown in the figure, the outermost layer of the material is wrapped by an amorphous carbon shell, and then the part close to the carbon shell is Fe3C structure, where the lattice fringe spacing of Fe3C in the R1 region is 0.210 nm, corresponding to the (211) crystal plane of Fe3C, and the lattice fringe spacing of Fe3O4 is 0.296 nm, corresponding to the (211) crystal plane of Fe3O4. The lattice fringe spacing of Fe3C in the R2 region is 0.206 nm, corresponding to the (102) crystal plane of Fe3C, and the lattice fringe spacing of Fe3O4 is 0.296 nm, corresponding to the (211) crystal plane of Fe3O4. 0 The lattice fringe spacing is 0.143 nm and 0.202 nm, corresponding to Fe 0 The (220) and (110) crystal planes of Fe3O4 are further extended into the material, and the lattice fringes of Fe3O4 appear with a spacing of 0.483 nm, which corresponds to the (111) crystal plane of Fe3O4. Therefore, the results of high-resolution transmission electron microscopy are consistent with the results of X-ray diffraction, further proving that the material is composed of Fe3O4, Fe 0 and Fe3C, and in a certain area, Fe3C acts as the outer layer of the catalyst, Fe 0 It is the middle layer and Fe3O4 is the core of the catalyst.

[0046] Application Examples Dissolve tetracycline in water to obtain a wastewater concentration of 10 mg / L, and then pour the wastewater into Figure 6In the reactor shown in FIG. 1 , the reactor uses a gas diffusion electrode as an auxiliary cathode to produce H2O2, and the electrodes provided in Examples 1-4 and Comparative Examples 1-3 are used as catalytic cathodes to produce ·OH, and air is used as an oxygen source. A DC power supply is turned on, and the current density of the gas diffusion electrode is controlled to be 2.5 mA / cm 2 and the current density at the catalytic cathode was 3.5 mA / cm 2 , the degradation time is 12 min.

[0047] See also Figure 7-9 The degradation effects of each embodiment and comparative example are as follows: like Figure 7 As shown, the removal rates of tetracycline by the electrodes provided in Examples 1-3 and Comparative Example 2 (in the figure, they are distinguished by the amount of acetic acid used) are 97.7%, 84.7%, 97.2% and 67.8%, respectively. The degradation process is fitted with the first-order reaction kinetic equation, and the reaction rates obtained are 0.277, 0.147, 0.283 and 0.092 min, respectively. -1 It can be seen that the reaction kinetic constant of the electrode obtained in Example 1 is increased by 3.0 times compared with that of Comparative Example 2.

[0048] Figure 8 The degradation effect of the electrodes provided in Examples 1, 4 and Comparative Example 3 on tetracycline. The removal rates are 97.7%, 97.0% and 35.1% respectively. The first-order reaction kinetic equation is used to fit the degradation process, and the reaction rates are 0.277, 0.276 and 0.033 min respectively. -1 It can be seen that the reaction kinetic constant of the electrode provided in Example 1 is increased by 8.4 times compared with that of Comparative Example 3.

[0049] Fig. 9 The results of the cyclic use test of the electric Fenton cathode provided in Example 1 of the present invention are shown in FIG. Fig. 9 After six cycles, the degradation efficiency of tetracycline still remained above 80%, indicating that the electrode has high stability.

[0050] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.

Claims

1. An electro-Fenton cathode based on MOF-derived carbon, comprising a penetrating electrode substrate and a MOF-derived carbon material located on the surface of the penetrating electrode substrate, wherein the MOF-derived carbon material comprises a carbon shell and a composite component in the carbon shell, characterized in that: The composite component includes Fe3O4, Fe 0 and Fe3C.

2. A method for preparing an electro-Fenton cathode based on MOF-derived carbon, characterized in that: include: Step 1: reacting a mixed system containing a penetrating electrode substrate, an iron source, an organic ligand, sodium hydroxide, a regulator, and a solvent to form an iron-based MOF material on the surface of the penetrating electrode substrate, wherein the regulator is used to regulate the surface morphology and defects of the iron-based MOF material; Step 2: calcining the penetrating electrode substrate with an iron-based MOF material formed on the surface obtained in step 1 to obtain an electric Fenton cathode based on MOF-derived carbon, wherein the specific conditions of the calcination include a calcination temperature of not less than 600°C.

3. The preparation method according to claim 2, characterized in that: The regulator is selected from at least one of formic acid, acetic acid and hydrofluoric acid; Based on the volume of the solvent being 100%, the amount of the regulator added is 0.1-30%.

4. The preparation method according to claim 3, characterized in that: The regulator is acetic acid, and the added amount of the regulator is 2-6%.

5. The preparation method according to claim 2, characterized in that: In step 1: The penetrating electrode substrate is selected from at least one of a stainless steel mesh, a copper mesh, a nickel mesh, a cobalt mesh, and a titanium mesh; The iron source is selected from at least one of ferric nitrate, ferric chloride and ferrous chloride; The organic ligand is selected from at least one of terephthalic acid, fumaric acid and trimesic acid; The solvent is selected from at least one of methanol, N,N-dimethylformamide and deionized water.

6. The preparation method according to claim 5, characterized in that: In step 1: The mass ratio of the iron source to the organic ligand is 0.5-5:1; The mass of the sodium hydroxide is 0.1 to 5 times that of the iron source; The mass of the solvent is 10 to 120 times that of the iron source.

7. The preparation method according to claim 2, characterized in that: The specific conditions of the reaction in step 1 include: The reaction temperature is 20~200℃; The reaction time is 2~200 h.

8. The preparation method according to claim 2, characterized in that: The specific conditions for calcination in step 2 include: Carry out under inert atmosphere; Calcination temperature is 600~1000℃; The calcination time is 0.5~10 h.

9. Use of the electro-Fenton cathode described in claim 1 or the electro-Fenton cathode prepared by the preparation method described in any one of claims 2 to 8 in catalytic degradation of antibiotics.

10. The use according to claim 9, characterized in that: The antibiotic is tetracycline.

Citation Information

Patent Citations

  • FeOx catalyst and its preparation method and use in prevention and control of environmental pollution

    CN106391017A

  • Metal organic framework derived iron-carbon catalyst suitable for heterogeneous electro-Fenton process and preparation method thereof

    CN111111661A

  • Prussian blue redox derived iron-based wave-absorbing material and preparation method thereof

    CN112492869A

  • Electro-Fenton catalyst derived based on iron-based metal organic framework and preparation method and application thereof

    CN113083369A

  • Preparation method and application of iron carbide / ferroferric oxide@carbon composite catalyst

    CN113991131A